Digitally-controlled H-bridge DC-DC converter for micropower PV energy harvesting system - Bui, Anh Khoa (2021)
This paper presents a micro-power photovoltaic (PV) harvesting system. A H-bridge configuration DC-DC converter is designed to harvest PV energy and deliver energy to applications of Internet of Thing (IOT). The main converter consists of a single inductor with two inputs and two outputs. It regulates a constant 1V output voltage for several applications such as sensors and signal transmitters. The surplus energy is stored in a rechargeable battery. The battery also serves as a secondary input source to provide energy to the output load in heavy-load condition. Due to the limited energy of the system, the power consumption of the power system is optimized by several techniques. A perturb-and-observe maximum power point tracker (MPPT) is implemented to maximize the power extracted from the PV harvester. Pulse-width modulation (PWM) and pulse-frequency modulation (PFM) are used to regulate the output voltage. The controller is designed mainly in digital and free of power-hungry circuits. The proposed converter occupies an area of 1.44mm2. The estimated peak power efficiency is 84% while driving 3-10μA load current.